2015
DOI: 10.1080/14689367.2015.1081380
|View full text |Cite
|
Sign up to set email alerts
|

Specification and partial hyperbolicity for flows

Abstract: We prove that if a flow exhibits a partially hyperbolic attractor Λ with splitting T Λ M = E s ⊕ E c and two periodic saddles with different indices such that the stable index of one of them coincides with the dimension of E s then it does not satisfy the specification property. In particular, every singular-hyperbolic attractor with the specification property is hyperbolic. As an application, we prove that no Lorenz attractor satisfies the specification property.1 for t ≥ 0. Now, take a small t 2 > 0 such tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Remark 4.12. Sumi, Varandas and Yamamoto [59] have shown that sectional-hyperbolic attractors (which include singular-hyperbolic attractors as a special 3-dimensional case) do not satisfy specification. Hence, the genericity of wild historic points is more general than the genericity of points with maximal oscillation in systems with specification.…”
Section: Now Let Us Considermentioning
confidence: 99%
“…Remark 4.12. Sumi, Varandas and Yamamoto [59] have shown that sectional-hyperbolic attractors (which include singular-hyperbolic attractors as a special 3-dimensional case) do not satisfy specification. Hence, the genericity of wild historic points is more general than the genericity of points with maximal oscillation in systems with specification.…”
Section: Now Let Us Considermentioning
confidence: 99%
“…The previous result can be understood as an extension of [27,Theorem A] where, analogously, the holonomy map along the strong unstable foliation plays a key role in the proof. In particular, a counterpart of this result for partially hyperbolic flows is expected to hold, in the spirit of [28].…”
Section: Statement Of the Main Resultsmentioning
confidence: 81%
“…Related results, on the characterization of the C 1 -interior of diffeomorphisms satisfying any of the previous properties, include [23,24]. However, most dramatically, if one considers the space of C r -diffeomorphisms, r ≥ 1, these two properties seldom occur in the absence of uniform hyperbolicity as proved in [9,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…be the global invariant manifold for x ∈ Λ. Then we have the following lemma which is [13,Lemma 3.7].…”
Section: Xiao Wen and Lan Wenmentioning
confidence: 99%